An algorithm for constructing all supercharacter theories of a finite group - Ashrafi, Ali Reza (Ars mathematica contemporanea, 2020)
In 2008, Diaconis and Isaacs introduced the notion of a supercharacter theory of a finite group in which supercharacters replace with irreducible characters and superclasses by conjugacy classes. In this paper, we introduce an algorithm for constructing supercharacter theories of a finite group by which all supercharacter theories of groups containing up to 14 conjugacy classes are calculated.
Keywords: conjugacy class; ireducibilni karakter; irreducible character; nadkarakterska teorija; nadrazred; odsek; supercharacter theory; superclass